PENINGKATAN MOTIVASI DAN AKTIVITAS BELAJAR PESERTA DIDIK MELALUI MODEL TALKING STICK PADA MUATAN IPA DI KELAS VI SDN 79/IV KOTA JAMBI - Prasetyo, Imam; Muhammad Sofwan; Indryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Motivation and learning activity are two essential aspects that influence the success of the learning process. However, many students still show low levels of motivation and limited engagement, particularly in science subjects, which are often perceived as difficult and less interesting. To address this issue, this study aims to improve students' motivation and learning activity through the implementation of the Talking Stick learning model. The research method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles. Data collection techniques include observation, motivation questionnaires, and learning outcome tests. The results show a significant improvement. In the first cycle, student motivation was recorded at 31.25%, and learning activity at 28.13%. After improvements in the second cycle, motivation increased to 78.13%, and learning activity reached 75%. The Talking Stick model proved effective in creating an interactive and enjoyable classroom atmosphere, as well as enhancing students’ confidence and active participation in the learning process